649 The role of cardiac rehabilitation in patients with atrial fibrillation and heart failure (Balneo and PRM Research Journal, 2024)
This review investigates the role and effectiveness of cardiac rehabilitation in individuals diagnosed with atrial fibrillation and heart failure. A comprehensive analysis of existing literature, clinical trials, and observational studies was conducted to assess the outcomes associated with cardiac rehabilitation interventions in this specific patient population. The complex and bidirectional relationship between atrial fibrillation and heart failure underscores the importance of a patient-centered approach that integrates medical, lifestyle, and rehabilitative interventions for optimal care and outcomes. Results suggest improved functional capacity, enhanced quality of life, and potential favorable cardiovascular outcomes. The review brings new insights to the existing literature, emphasizing the importance of personalized cardiac rehabilitation strategies in optimizing the overall well-being of these patients.